Prinsip-Prinsip Manajemen Syariah - Muhammad Nizar (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2018)
Statistical data show that the number of cooperatives in Indonesia in 2017 reached 153,171 units, with active members recorded at 26.53 million. Among the data is the name Koperasi Syariah Fatayat NU Purwodadi District Pasuruan Regency. This cooperative was established in 2016, with 3 employees in it, because the cooperative is relatively young, so for the sake of sustainability it must have good management, even sharia-based management, because it belongs to Islamic cooperatives. The purpose of this study is to give an overview, that management is a very important thing, with good management, the Koperasi Syariah Fatayat NU in Purwodadi Pasuruan Subdistrict is also getting better.